DIGITAL TRANSFORMATION AND BUSINESS MODEL INNOVATION: INSIGHTS FROM MULTINATIONAL COMPANIES IN SOUTH-SOUTH NIGERIA - U. Omodafe, Philomena; Akpevwe Onobrakpeya, Stanley (African Journal of Social and Behavioural Sciences, 2024)
This study examined the effect of digital transformation on business model innovation among multinational companies in South-South Nigeria. Utilizing a quantitative approach with a cross-sectional survey, data were collected from a sample of 384 respondents with digital expertise. Analysis revealed that digital transformation significantly drives business model innovation, with big data analytics having the strongest influence, highlighting the value of data-driven decision-making. Digital assets play a key role in developing new business models, while digital agility and networking capabilities support flexibility and collaboration. With 62% of business model innovation explained by digital transformation variables, the study recommends investing in digital infrastructure, fostering agility, enhancing collaboration, and leveraging advanced analytics to stay competitive.